Social Stigma Towards People with Mental Illness: A Study Among Nepalese University Students - Karki, Raj; Raut, Sunita; Dahal, Birendra Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Social stigma towards people with mental illness (PWMI) involves society’s endorsement of stereotypes, prejudice, and discrimination directed at PWMI. From a sociological perspective, stigma and mental illness are not only experienced at the individual level, but they are also socially constructed phenomena shaped by cultural norms, institutional practices, and power dynamics that serve particular social functions such as maintaining social order, reinforcing norms, and managing perceived threats. This study aimed to examine the association between social stigma towards PWMI and both education/training related to mental health and contact with PWMI. A quantitative cross-sectional design was employed, and data were collected from 246 master’s-level students at Tribhuvan University, Nepal, using socio-demographic questions, along with the CAMI and the RIB scales. Findings of this study revealed a statistically significant (p < 0.01 and Cramer’s V > 0.2) associations between stigmatizing attitudes and both education/training and contact. Notably, direct contact was more strongly associated with positive attitudes than indirect contact. The findings also showed that students who had both education/training and contact, exhibited more positive attitudes towards PWMI than those with only one or neither. These positive attitudes stem from the roles that both education/training and contact play in challenging and reducing stereotypes. This is supported by Link and Phelan’s model of the stigmatization process, which posits that stereotypes precede negative attitudes such as prejudice and discrimination. Additionally, reduction in stereotypes also diminishes the perceived need for stigma’s social functions, thereby making the maintenance of mental illness stigma less necessary.